100k views
2 votes
Drag each expression to show whether it is equivalent to 36x + 9, 9(4x – 1), or (4 • 9x) + (4 • 2).

Drag each expression to show whether it is equivalent to 36x + 9, 9(4x – 1), or (4 • 9x-example-1

2 Answers

4 votes

Answer:

The equivalent expressions are:


36x + 9=(9\cdot 4x) + (9\cdot 1)=9(4x + 1)


9(4x-1)=36x-9=(3\cdot 12x)-(3\cdot 3)


(4\cdot 9x)+(4\cdot 2)=4(9x+2)=36x+8

Explanation:

Consider the provided expressions.


36x + 9

The expression
36x + 9 can be written as:


36x + 9=(9\cdot 4x) + (9\cdot 1)


36x + 9=(9\cdot 4x) + (9\cdot 1)=9(4x + 1)

Consider the expression
9(4x-1)

The expression
9(4x-1) can be written as:


9(4x-1)=36x-9

Take 3 common.


9(4x-1)=36x-9=(3\cdot 12x)-(3\cdot 3)

Consider the expression
(4\cdot 9x)+(4\cdot 2)

The expression
(4\cdot 9x)+(4\cdot 2) can be written as:

Take out 4 common


(4\cdot 9x)+(4\cdot 2)=4(9x+2)

Open the parentheses.


(4\cdot 9x)+(4\cdot 2)=4(9x+2)=36x+8

User Kekkeme
by
6.7k points
5 votes

Start with expressions in blue boxes:

1st column)
36x+9;

2nd column)
9(4x-1)=36x-9;

3rd column)
(4\cdot 9x)+(4\cdot 2)=36x+8.

You have 6 expressions. Consider all them:

1.
36x+8 - 3rd column;

2.
(9\cdot 4x)+(9\cdot 1)=36x+9 - 1st column;

3.
(3\cdot 12x)-(3\cdot 3)=36x-9 - 2nd column;

4.
9(4x+1)=36x+9 - 1st column;

5.
36x-9 - 2nd column;

6.
4(9x+2)=36x+8 - 3rd column.

User Probablykabari
by
5.9k points